Applying distribution of feature points to detect multiple plane. (2nd March 2012) - Zhao, Lugang; Wu, Chengke
For detecting multiple planar regions rapidly in the image sequence, this paper proposed a novel algorithm. First of all, the method uses RANSAC to detect a dominant homography, then, it calculates the poles corresponding to the two images based on homography constraint and classifies all the matching feature points into two sets. When we detect the homography corresponding to more planes based on RANSAC once more, only three pairs of feature points should be selected from the classified feature points, that is define the to-bedetermined plane homography model together with a pair of poles, and this can improve the detection efficiency. Simulation and real experiment results show that the proposed algorithm is robust to the existence of mismatched features and is applicable to either stereo or motion sequence images.